Perturbations of a Class of Ordinary Differential Expressions Preserving the Essential Spectrum and the Nullities - Mumpar-Victoria, Marie Redina (Science Diliman: A Journal of Pure and Applied Sciences; Vol 11 No 1 (1999), 2007)
Excerpt Perturbation is used to enlargen a class of differential expressions for which the essential spectrum and the nullities can be classified.